2011
DOI: 10.1590/s1413-35552011005000014
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence and perineal muscle function in physically active and sedentary elderly women

Abstract: Objective: To identify the presence of urinary incontinence and compare perineal muscle function among physically active and sedentary older women. Methods: The sample consisted of 39 elderly women, 28 of whom got regular physical activity (AG) and 11 did not (SG). We collected data on risk factors for pelvic floor weakness and the presence of urinary incontinence (UI). The evaluation of perineal function was performed using PERFECT and perineometry. The data were processed with descriptive (simple frequencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
1
14
0
5
Order By: Relevance
“…9 Furthermore, in relation to the BMI and WC of physically active older women, the study found that these anthropometric measurements are not a risk factor associated with UI in this population. 27 Another important factor is that the perceived aerobic capacity (able to run for 30 minutes) is associated with better muscle function of the pelvic floor (OR ¼ 1.63; 95%CI 1.27-2.09), 28 which can reduce the association between these anthropometric variables and the presence of UI.…”
Section: Discussionmentioning
confidence: 99%
“…9 Furthermore, in relation to the BMI and WC of physically active older women, the study found that these anthropometric measurements are not a risk factor associated with UI in this population. 27 Another important factor is that the perceived aerobic capacity (able to run for 30 minutes) is associated with better muscle function of the pelvic floor (OR ¼ 1.63; 95%CI 1.27-2.09), 28 which can reduce the association between these anthropometric variables and the presence of UI.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect related to UI is that regular physical activity helps to reduce body weight, which is an important risk factor in the genesis of UI 12 and minimizes the decline in muscle strength, including pelvic floor muscles (PFM) in older women 11 . Lee and Hirayama 19 assessed the relationship of physical activity with UI and found that the practice of walking an average of 5 hours a week is a protective factor for UI (OR = 0:43; CI 95% = 0.20-0.96) and Kikuchi et al 16 analyzed the relationship of physical activity in the leisure domain with UI and found that moderate (OR = 0.63; CI 95% = 0.42-0.94) and high levels (OR = 0 43; CI 95% = 0.26-0.68) of physical activity are protective factors for UI.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies claim that the practice of moderate physical activity can minimize the reduction in the strength of pelvic floor muscles 11 or even reduce the occurrence of UI with increasing age 12 . Thus, it was observed that the level of scientific evidence on the influence of physical activity on urinary incontinence is still undefined and bidirectional 13 , as it may be a risk factor (OR = 1.37; CI 95% = 1.09-0.71) 15 or a protection factor for urinary incontinence (OR = 0.62; CI 95% = 0.44-0.89) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Although it is known that UI is associated with decreased mobility [8] and that older women performing physical exercise have better pelvic floor muscle function than their sedentary peers [9], it is necessary to determine whether older women with UI lose urine when performing resistance exercise at different intensities (moderate and vigorous). Therefore, the objective of this study was to evaluate the acute effect of resistance exercise performed at different intensities (moderate and vigorous) on urine loss in older women with mixed and stress UI.…”
Section: Introductionmentioning
confidence: 99%